Academic and financial benefits for student-athletes at a Brazilian Federal University - Vagner Pereira da Silva, Junior; Caiçara de Albuquerque, Alex (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The University is configured in a complex context. It encompasses a set of diverse people, among them the student-athletes, who, in addition to undergoing the academic activities inherent to the formation, still face the workload of training and competitions. Policys have been developed with specialized assistance to provide better conditions to the public. The aim of this study was to investigate the granting of academic and financial benefits to student-athletes at a Brazilian Federal University. This was an exploratory documentary research, with the technique of document analysis applied to resolutions, service instructions, ordinances, and proclamations. The results indicated that the University has policys for dual careers, although they are limited to academic and sports initiatives. The policys is materialized through standard rules and granting absence allowances to student-athletes in competitions representing the University, a monthly sports scholarship (R400.00) and financial aid for participation in competitions with an individual value of R800.00. It is concluded that the institution promotes dual careers through policies, although this is restricted, imprecise, and limited in academic initiatives; partially adequate in sports initiatives, with urgent readjustments needed in the value of the scholarship and the creation of actions aimed at retirement preparation.